2017
DOI: 10.1002/ece3.3463
|View full text |Cite
|
Sign up to set email alerts
|

Spatially varying density dependence drives a shifting mosaic of survival in a recovering apex predator (Canis lupus)

Abstract: Understanding landscape patterns in mortality risk is crucial for promoting recovery of threatened and endangered species. Humans affect mortality risk in large carnivores such as wolves (Canis lupus), but spatiotemporally varying density dependence can significantly influence the landscape of survival. This potentially occurs when density varies spatially and risk is unevenly distributed. We quantified spatiotemporal sources of variation in survival rates of gray wolves (C. lupus) during a 21‐year period of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 87 publications
(137 reference statements)
3
18
0
Order By: Relevance
“…In contrast, IPD or IDD should lead to differences in average fitness between habitat classes. Although we could not analyse metrics of fitness such as reproductive success in this study, analyses of adult survival within the same population indicated that survival varied spatially and was reduced in agricultural areas (O'Neil et al, 2017; Stenglein, Gilbert, et al, 2015). In addition, there were several observations of intraspecific killing in this population and adjacent populations (O'Neil, 2017; Stenglein et al, 2015), suggesting territorial interference.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, IPD or IDD should lead to differences in average fitness between habitat classes. Although we could not analyse metrics of fitness such as reproductive success in this study, analyses of adult survival within the same population indicated that survival varied spatially and was reduced in agricultural areas (O'Neil et al, 2017; Stenglein, Gilbert, et al, 2015). In addition, there were several observations of intraspecific killing in this population and adjacent populations (O'Neil, 2017; Stenglein et al, 2015), suggesting territorial interference.…”
Section: Discussionmentioning
confidence: 84%
“…This scenario is most likely to arise when two major elements of habitat selection are prey abundance and the risk of human‐caused mortality, a common circumstance for populations of large carnivores. In such cases, density‐dependent mortality due to humans (Murray et al, 2010) and other factors would create an uneven landscape mosaic of fitness (O'Neil, Bump, & Beyer, 2017; Smith et al, 2010; Stenglein, Gilbert, Wydeven, & Deelen, 2015). If individuals respond to spatially varying mortality risk according to the IPD, the prediction would be that high‐risk sites are selected only after low‐risk sites have become occupied.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true at high density, but, crucially, when territories nearly saturate the landscape, closure assumption violations are less consequential, and tend to offset each other for adjacent sample units. In both Wisconsin and elsewhere, it is likely that wolf home ranges are aggregated in the highest quality habitat where mortality risk is lowest, to the extent that these areas are nearly saturated (Mladenoff 2009, O'Neil et al 2017). Montana uses a large (600 km 2 ) sampling grid resolution, multiple state‐wide observation data sources, and informative landscape covariates to predict occupancy of wolves and scale up to abundance (Rich et al 2013, Montana Fish, Wildlife, and Parks 2018), and most occupied sample units are aggregated in the western part of the state (Rich et al 2013: figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, the state adopted a geographically stratified sampling plan to reduce the cost and effort of the survey. A panel design was implemented to increase the precision of abundance estimates which ensured that some sampled units were counted during successive years [48,50].…”
Section: Methodsmentioning
confidence: 99%